Feeding high levels of wet corn gluten feed to dairy cattle - Mullins, Chad Ryan (Kansas State University, 2009)
Increased pressure for land use and greater demand for cereal grains have substantially increased feed costs for dairy producers. This has forced nutritionists to devise novel diet formulation strategies to help keep feed costs in check. As a result, dairymen are incorporating wet corn gluten feed (WCGF) into diets. Numerous studies have reported production responses to dietary inclusion of WCGF, but few have reported ruminal effects. Therefore an experiment was conducted to monitor production, while simultaneously measuring ruminal fermentation and total-tract digestion in 8 Holstein cows fed 0, 12, 24, and 36% WCGF (DM basis). Results from this study were consistent with recently published papers indicating that increasing dietary levels of WCGF linearly increases milk and milk component production. However, results demonstrate that this increase in production is related to an increase in feed intake, not improved digestibility. In addition to escalating grain prices, recent pressure for land and water use has led to a decrease in the availability of alfalfa. A second experiment was conducted to determine if forage fiber provided by alfalfa hay is necessary to maintain production in diets containing 31% WCGF (DM basis). Eighty primiparous and multiparous Holstein cows were utilized in two 4 × 4 Latin squares to evaluate the effects of feeding alfalfa at 0, 7, 14, and 21% of diet DM. Feeding higher proportions of alfalfa tended to increase ECM yield and decrease BW gain, suggesting that metabolizable energy supply was repartitioned from BW gain to milk production as more alfalfa was included. However, partial budget analysis determined that decreasing alfalfa inclusion rate may improve farm profitability by reducing feed costs and expenses associated with manure handling, despite small losses in productivity. Overall, these research projects suggest that large proportions of WCGF can effectively be fed to dairy cattle without sacrificing milk production, even without the use of alfalfa hay. Therefore, WCGF can be a cost-effective alternative to traditional dietary ingredients.
Keywords: By-product; Dairy cattle; Wet corn gluten feed; Alfalfa; Agriculture, Animal Culture and Nutrition (0475)